2021
DOI: 10.1016/j.jsps.2021.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist insulin injection re-education on glycemic control among type II diabetic patients in primary health clinics

Abstract: Background Insulin injection technique re-education and diabetes knowledge empowerment has led to improved glycemic control. Objectives To evaluate the impact of pharmacist’s monthly re-education on insulin injection technique (IT), lipohypertrophy, patients’ perception on insulin therapy and its effect on glycaemic control. Methods This randomized controlled, multi-centered study was conducted among type 2 diabetics from 15 government health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Some of the studies in the systematic reviews showed that better outcome could be achieved by manage the patients' adherence [12]. Counselling and re-education for insulin injection can be provided to the T2DM patients to increase their adherence and improving the HbA1C [13]. The other systematic review and meta-analysis also stated that psychological intervention may be provided to the T2DM patients to improve patients' adherence and to lower HbA1C, beside telecare and educational interventions [14].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies in the systematic reviews showed that better outcome could be achieved by manage the patients' adherence [12]. Counselling and re-education for insulin injection can be provided to the T2DM patients to increase their adherence and improving the HbA1C [13]. The other systematic review and meta-analysis also stated that psychological intervention may be provided to the T2DM patients to improve patients' adherence and to lower HbA1C, beside telecare and educational interventions [14].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of our study, illiterate participants had a higher negative risk perception of insulin therapy ( p < .001; Table 3). Some studies in the literature have indicated that education affects negative attitudes and perceptions of insulin therapy (Batais & Schantter, 2016; Brod et al, 2009; Saleem et al, 2016; Sürücü et al, 2017; Wong et al, 2011), whereas others have stated the opposite (Ayanoğlu, 2020; Chen et al, 2011; Polat et al, 2017; Selvadurai et al, 2021). In our study, it was determined that housewives had a higher negative risk perception of insulin therapy ( p < .001; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, providing education and feedback to patients can significantly improve their injection technique and diabetes management [ 9 12 ]. Better access to education resources is necessary to enhance diabetes control and outcomes [ 13 16 ]. For instance, the latest Forum for Injection Technique (FIT) recommendations were developed in Canada in 2020 as a blueprint for best practice in injection technique for all diabetes care providers [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%